Effect of dietary natural extracts mixture on rabbit does reproductive performances: preliminary data. (International Journal of Health, Animal Science and Food Safety, 2017)
In the recent years, research has focused the attention on the use of substances able to improve both animal health and meat quality. The objective of this study was to investigate the effect of dietary supplementation with natural extracts in rabbit does on reproductive parameters. Natural extracts have been widely reported to have potent antioxidant, anti-inflammatory and antimicrobic activities related especially to their phenolic content (Pereira et al., 2009). In rabbit production, does are normally inseminated 11 days after parturition, with kits being weaned at 35 days (Rebollar et al., 2006). The reproductive phase is a critical period because the animals have few days to reconstitute their body reserves (Castellini et al., 2003).  Therefore, the interaction between nutrition and reproduction is crucial in this specie (Butler, 2000; Roche et al., 2000). The trial was performed at the Research Institute for animal production in Nitra (Slovak Republic). Sixty does were randomly selected, artificially inseminated and divided into three experimental groups. The first fed a basal diet (C), the second one (T1) received 0.3% of natural extracts mixture and the third one (T2) an integration of 0.6% of natural extracts mixture for gestation and lactation period (65 days) The animals were allocated in individual flat-deck cages with a closeable nest box. At parturition, the total number of kits born and stillborn and litters weights were recorded. The data were analyzed by one way Analysis of Variance (ANOVA) using SPSS (IBM.-SSPS Statistics 24). Dietary supplementation did not affect (P>0.05) number of kids born (8.0 ± 1.0 C vs 7.3 ± 0.97 T1 and 7.4 ± 1.0 T2) and birth weight (63 ± 2.0 g C vs 60.1 ± 2.3 g T1 and 61.0 ± 2.4 g T2).  The administration of natural extract in does did not improve (P>0.05) the kits average daily gain (20.54 ± 1.3 g/d C vs 21.92 ± 0.5 g/d T1 and 20.93 ± 0.9 g/d T2) and body weight at weaning (829 ± 16.6 g C vs 834 ± 26.6 g T1 and 826 ± 26.8 g T2). These preliminary data showed that at the present dosage, the natural extracts mixture is not able to affect does reproductive performance. However, further research is needed to confirm the present data and explore the mechanism of action of this natural mixture.
Keywords: Dietary supplementation; Natural extracts; Nutrition; Rabbit does; Reproduction